Tasawuf dalam Pandangan Ibnu Taimiyah: Maqamat dan Ahwal - Mohammad Muaffan, muaffan (Mahad Aly Al Fithrah, 2021)
Ibn Taimiyyah is known as give acute criticism to behavior and thought of popular Sufism which considered contrary with Qur'an and al-Hadith. But the true one, Ibn Taimiyyah did not attack all precepts Sufi, and he still acknowledged the existence of Sufism itself. Thus, Ibn Taimiyyah certainly admit the validity experimental method of Sufism, but he suggested that Sufism also use external validity to test the truth of concept. External validity that mean is precept that exists in Islamic. This research is literature. The data unearthed in this study is the thoughts and views in the opus of Ibn Taimiyyah as the object of this research. The result of this study is Ibn Taimiyyah's view about Sufism reveals that Sufism is an extension of the Islamic religion which normatively must be derived from Qur'an and Sunnah also historically applicative should revert to example of companions. Some of ibn Taimiyyah's writings talk about deeply Sufism are already covered in the classical book Majmu' al-Fatawa which is a collection writings from Ibn Taimiyyah.